Health, nutrition and food demand - Chern, W. S.; Chern, W. S.; Rickertsen, K.; Rickertsen, K. (Wallingford :CABI Publishing, 2003)
This book discusses the likely impacts of health information on the demand for various foods in various countries and among various socioeconomic groups. The effects of types of information such as food scares related to mad cow disease and advertising are also discussed. The book serves as reference for researchers in the food industry and government, as well as a supplementary textbook in courses in applied microeconomics, consumer demand, health economics and food consumption and nutrition. The book is based on papers presented in the mini-symposium on 'Effects of Health Information on the Demand for Food: EU and US Experiences' organized as part of the XXIV International Conference of Agricultural Economists held in Berlin, Germany during 13-18 August 2000.
Keywords: EE116 - Food Economics, (New March 2000); EE720 - Consumer Economics; VV100 - Human Nutrition (General); USA